Spirituality as a Predictor for Fear of Recurrence Among Cancer Patients - Ali, Abid; Khan, Imran; Ullah Khan, Ihsan (The Journal of Humanities & Social Sciences, 2023)
This study's primary objective was to evaluate the impact of spirituality on the fear of cancer recurrence among cancer patients. A structured interview schedule was used and data from 200 cancer patients were collected employing a purposive sampling technique. SPSS V-20 was used to analyze the data. For the demographic information, simple percentages, frequency, and mean scores were employed. The relationship between the variables was examined by using Pearson's correlation test. The results show that most of the cancer patients (75%) were men in the age range of 49 to 58 (35%), were single (58%), and (42%) were members of joint families. According to the clinical feature data, stage III (38%), patients were found in the majority, throat cancer (12%), while 80% had no family history of the disease. According to an analysis of patients' spirituality, the majority (37%) were extremely spiritual people, and (36%) used the recital of sacred Quranic verses to promote healing. According to the univariate analysis, total spirituality received a higher mean score (M=2.4) and FCR (M=2.60). In a correlation study, spirituality shows a substantial negative relation (r=-0.65; p=.000) with fear of relapse and a significant positive link (r=0.485; p=.000) with intrusiveness. The findings also show a negative and significant relationship between the independent variable and FCR in patients (r= -0.532; p=.000). The study concludes that patients performed various spiritual practices as a supportive mechanism to avoid the fear of recurrence. This study recommends that healthcare professionals need to understand the significance of spirituality as an essential coping therapy and provide holistic care to reduce cancer patients' FCR. Keywords: Cancer recurrence, Fear of recurrence